Social Support, Social Networks, and Happiness of Individuals With Visual Impairments. (July 2015) - Papadopoulos, Konstantinos; Papakonstantinou, Doxa; Koutsoklenis, Athanasios; Koustriava, Eleni; Kouderi, Vasiliki
The purpose of this study was to examine the structure of active social networks of individuals with visual impairments, the social support they receive from their social networks, and their satisfaction from received support. In addition, we examined these factors as predictors of happiness in people with visual impairments. A total of 96 individuals with visual impairments, who ranged in age from 16 to 50, participated in this study. Three self-constructed questionnaires, which included questions related to demographic data, social networks, social support, and happiness, were used in the study. Participants reported being satisfied with received support, and they also appeared to receive more positive than negative support. Findings also demonstrated the merit of social support for the happiness of individuals with visual impairments.